The Attractiveness of Hydroponics for Millenial Youth Organization at Cibeunying Kidul Bandung - et. al., Ayuningtyas Y. Hapsari, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Hydroponics is a modern way of farming today, although currently the majority of hydroponic farmers are over 40 years old. but not infrequently many millennial generations start to look at this business, they are no longer ashamed to farm because they use very modern methods. hydroponic business actors among millennials, if given training and high motivation, will bring huge profits. and can support the Green Environment concept because it is very environmentally friendly. This research is aimed at members of the Youth Organization in the Cibeunying Kidul area who have previously received training in farming using hydroponic methods, but they have not been motivated to become a real hydroponic business actor, this is also caused by the less supportive organizational environment around them. By distributing a sample of 42 respondents, then the results of the questionnaire are processed using descriptive verification methods, it can be concluded that training and the organizational environment have a significant influence on the motivation of members of the youth organization to become entrepreneurs in the hydroponic field.